Using environmental tracers and modelling to identify natural and gas well-induced emissions of methane into streams. (April 2018) - Grieve, P.L.; Hynek, S.A.; Heilweil, V.; Sowers, T.; Llewellyn, G.; Yoxtheimer, D.; Solomon, D.K.; Brantley, S.L.
Abstract: Development of shale gas wells sometimes results in migration of methane (CH4 ) from boreholes into aquifers. Identification of leakage has relied on analysis of CH4 in individual groundwater samples, usually from water wells; however, collection of point data is expensive and prone to artefacts. Methane analysis in streams is a novel way to find potential leakage of CH4 to groundwater. Here, dissolved hydrocarbons and geochemical tracers were measured in streams during base flow in watersheds with high densities of shale gas wells in Pennsylvania (PA) to identify characteristics related to leaking gas wells. Three streams with no known contamination from gas wells and one stream near a gas well previously reported to be leaking CH4 were investigated. The characteristics observed in the stream near the putatively leaking gas well that distinguish it from the streams without leaks include higher CH4 concentrations in riparian groundwater (as high as 4600 versus 206 μg/L), a relatively high gas influx to the stream channel (>70 versus <10 mg m −2 d −1 ), hydrocarbon isotopic signatures and radiogenic strontium consistent with Middle Devonian Marcellus Formation shale, and higher concentrations of modern atmospheric age tracers in groundwater. These tracer concentrations may indicate upward transport of hydrocarbons as a separate gas phase rather than in solution. In addition, the stream near the putatively leaking well was not located along a fault-related topographic lineament whereas streams with substantial natural thermogenic CH4 influxes tend to be aligned with potential geologic structures. The stream approach is an efficient technique to estimate watershed-scale groundwater compositions and fluxes of CH4 that reveal natural and anthropogenic sources of methane emissions. Highlights: Thermogenic methane enters streams along fractures in the Appalachian Basin. Gaining streams collect upwelling methane and reveal watershed-wide gas fluxes. Hydrocarbons, tracers, and salts in some streams may fingerprint leaking gas wells.